Hands-on Kubernetes on Azure : automate management, scaling, and deployment of containerized applications /: automate management, scaling, and deployment of containerized applications. (2020) - Franssens, Nills; Gopalakrishnan, Shivakumar; Lenz, Gunther
No abstract available